Sustainable urban growth patterns based on environmental fitness - Ugalde-Monzalvo, Marisol (Frontiers in Sustainable Cities, 2024)
This study examines the sustainability of urban growth, described by patterns of environmental fitness. The main assumption is that resources use – energy, materials, electricity, water, fossil fuels, soil, human – describe growth patterns whose sustainability can be categorized according to environmental fitness, which is assessed by the availability of environmental resources (characteristics of the environment), and the adaptation of the city to this availability (characteristics of the built environment). The article offers an innovative perspective by proposing a model for categorizing the sustainability of urban growth based on environmental fitness, but also by providing a mean to understand the city as a process and the city as a satisfier of needs. The methodology comprises two parts: 1) creating a matrix of indicators of urban environmental fitness, and 2) constructing an urban growth sustainability index. From this methodology, six patterns emerged: I) Economizing growth: Available resources with maximum urban adaptation; II) Weak growth: Availability of resources with minimal urban adaptation; II) Efficient growth: Availability of resources with appropriate urban adaptation; IV) Deficient growth: Availability of resources without urban adaptation; V) Efficient growth and of investment: Lack of resources with urban investment; and VI) Deficient growth and of degradation: Lack of resources with urban deterioration and wear. The finding of these sustainable urban growth patterns demonstrates the concrete application of environmental adaptation theories and an understanding of the global behavior of cities. The empirical results support the assertion that urban growth presents challenges and potentials in terms of reduction, reuse, and recycling, of urban sprawl, urban renewal, redevelopment and infill growth, the efficiency and maintenance of urban infrastructure as guidelines for urban sustainability.